Peace Building: Tantangan Dakwah di Era Disrupsi - Nahed Nuwairah (UIN Antasari Banjarmasin, 2020)
Since the global challenges of da’wah getting more and complex, it is necessary for the preachers to understand strategic steps to consider before doing da’wah. Including in Indonesia as a country that has so many diversity of etnicities, tribes, languages, religions and cultures. Realizing an atmosphere of harmony in Indonesian society requires the togetherness of various community parties, including preachers who bear the responsibility for reflects the values of Islam as rahmatan li al-‘alamin. This paper mainly focused on how do da’wah that can be applied in Indonesia as a nation unity in diversity (Bhinneka Tunggal Ika) in order to building peace facing the disruption era. Regarding to the disruption era, the da’wah approach will require changes and adjustment, both regarding the form, media, content (message) and underlying paradigm. The author offers some strategies, there are strengthening family, fostering common perceptions among community groups by strengthening universal values and developing an information system that is able to reach people widely and foster effective and harmonious communication. Of course, this writing accompanied by hope that there will be an effort to elaborate it systematically in the future.